The Role And Place Of Parliamentarism in The Democratization And Reform Of Society - Yusupov Kamoliddin Mamatkulovich (International Journal of Advanced Science and Technology, 2020)
The formation and functioning of a bicameral parliament in Uzbekistan has marked a new stage in further improving the legal framework for reforms in the judiciary, economy and other spheres of life. The first President Islam Karimov stated at a joint meeting of the Oliy Majlis, the Legislative Chamber and the Senate of the Republic of Uzbekistan on January 28, 2005 that "the most important task in state building and governance is to strengthen the role and influence of the legislature."